The Degree to Which Computer Teachers at the Secondary Stage Possess Blended Learning Competencies - Al-Otebi, Sarah Zaid; Al-Sahim, Ashwaq Abdellah (Journal of Educational and Psychological Sciences, 2023)
The research aimed to identify the degree of possession of computer teachers at the secondary level of the competencies of blended learning. To achieve the goal of the research, the researchers used the descriptive approach, and a blended learning competency scale was used as a tool for data collection. After verifying its validity and reliability, it was applied to a sample of (235) computer teachers in the secondary stage in Riyadh. The results revealed that computer teachers possess blended learning competencies to a high degree. The attitudes dimension came first, followed by online integration, personalization and online interaction, and finally data-related practices as the least possessive dimensions for computer teachers. The results also indicated that there were no statistically significant differences in the responses of the sample due to the variables of years of experience and educational qualification. Considering these results, the two researchers recommended several recommendations, namely: continuing to develop blended learning competencies for computer teachers through workshops and training courses in line with the needs of teachers, focusing on the competencies of data practices, motivating female teachers to apply blended learning by equipping laboratories, connecting schools to the Internet, and encouraging them to integrate technology in the educational process.